Human induced pluripotent stem cell derived nanovesicles for cardiomyocyte protection and proliferation - Yuhua Wei; Xiaoxiao Geng; Qing You; Yu Zhang; Fangfang Cao; Gunaseelan Narayanan; Thanh Nguyen; Xiaoyuan Chen; Jianyi Zhang; Lei Ye (Bioactive Materials)
It remains a significant challenge to reactivate the cell cycle activity of adult mammalian cardiomyocytes (CMs). This study created a hypo-immunogenic human induced pluripotent stem cell (hiPSC) line using clustered regularly interspaced palindromic repeats (CRISPR)/Cas9 gene editing to knockout β2-microglobulin in hiPSCs (B2MKOhiPSCs) for manufacturing nanovesicles (B2MKOhiPSC-NVs). Approximately 9500 B2MKOhiPSC-NVs were produced from a single B2MKOhiPSC. Proteomic analyses indicated that, compared to B2MKOhiPSCs, the cargos of B2MKOhiPSC-NVs were enriched in spindle and chromosomal proteins, as well as proteins that regulate the cell cycle and scavenge reactive oxygen species (ROS). When administrated to hiPSCs derived CMs (hiPSC-CMs), B2MKOhiPSC-NVs reduced lactate dehydrogenase leakage and apoptosis in hypoxia-cultured hiPSC-CMs through activating the AKT pathway, protected hiPSC-CMs from H2O2-induced damage by ROS scavengers in the NV cargo, increased hiPSC-CM proliferation via the YAP pathway, and were hypoimmunogenic when co-cultured with human CD8+ T cells or delivered to mice. Furthermore, when B2MKOhiPSC-NVs or 0.9 % NaCl were intramyocardially injected into mice after cardiac ischemia/reperfusion injury, cardiac function and infarct size, assessed 4 weeks later, were significantly improved in the B2MKOhiPSC-NV group, with increased mouse CM survival and cell cycle activity. Thus, the proteins in the B2MKOhiPSC-NV cargos convergently activated the AKT pathway, scavenged ROS to protect CMs, and upregulated YAP signaling to induce CM cell cycle activity. Thus, B2MKOhiPSC-NVs hold great potential for cardiac protection and regeneration.